2012
DOI: 10.1097/01.naj.0000415957.46932.bf
|View full text |Cite
|
Sign up to set email alerts
|

Original Research

Abstract: Social and organizational factors appear to play critical roles in nurses' adoption and use of guidelines. Health care leaders seeking to improve clinical practice guideline use among nurses should ensure that facilitators and barriers-particularly those that are social and organizational-are considered and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…One of the most commonly reported barriers to use of PROs or implementation of other best practice guidelines is a perception of the burden of time required to do so properly [8,9]. The original NDI comprises 10 domains, each with 6 statements that are to be read by the respondent, who then chooses the one statement that most closely represents his/her current functional status within each domain.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly reported barriers to use of PROs or implementation of other best practice guidelines is a perception of the burden of time required to do so properly [8,9]. The original NDI comprises 10 domains, each with 6 statements that are to be read by the respondent, who then chooses the one statement that most closely represents his/her current functional status within each domain.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 summary of systematic reviews of the impact of AH care on stroke rehabilitation outcomes showed significant economic benefits [ 12 ]. Key barriers to implementing evidence-based AH rehabilitation in SA are similar to those reported in high-income countries (for instance lack of workforce, training, support, resources and recognition of effort) [ 8 , 9 , 13 ]. However, there are also unique SA-context facilitators which mediate some of these barriers to improve AH rehabilitation, including the innovative use of resources and informal AH rehabilitation networks with the common goal of improving functioning and quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 71%
“…Much of this research has focused on why so much difficulty is experienced by policy-makers, managers and clinicians in implementing evidence into practice [ 6 ]. Across health disciplines, there are generally positive attitudes to using evidence in practice, and despite discipline-differences in competencies and scope of practice, similar reasons emerge for not actually doing so [ 7 , 8 ]. Commonly, these are lack of time, ready access to CPGs, understanding about different forms of evidence recommendations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that not only the content is important for delivering proper care, but the protocol must be feasible and have a clear structure for the direct caregivers as well [ 19 ]. Improved compliance with protocols is found if there are comprehensive protocols, especially if nurses are involved in the development of these protocols [ 1 ]. In our study the structure of the studied protocols differed greatly whereas the TH scored lower than the other two types of hospitals.…”
Section: Discussionmentioning
confidence: 99%